Adherence to the Mediterranean Diet and Successful aging in Greeks living in Greece and abroad: the epidemiological Mediterranean Islands Study (MEDIS). Issue 2 (June 2023) - Papadimitriou, Anastasia; Foscolou, Alexandra; Itsiopoulos, Catherine; Thodis, Antonia; Kouris-Blazos, Antigone; Brazionis, Laima; Sidossis, Amalia C.; Polychronopoulos, Evangelos; Kokkinos, Peter; Panagiotakos, Demosthenes; Sidossis, Labros S.
Background: Whether older immigrant populations from the Mediterranean region, continue to follow the MD long after they immigrated is not known.Aim: Compare adherence to the MD and successful aging levels between Greeks living in Greece (GG) and Greeks living abroad (GA).Methods: Anthropometrical, clinical, psychological, sociodemographic, dietary and lifestyle parameters were assessed in a cross-sectional manner in a sample of 252 GG and 252 GA. Mediterranean Diet Score (MedDietScore range 0-55) was used to assess adherence to the MD. Successful aging was evaluated with the validated successful aging index (SAI range 0-10).Results: GA presented higher adherence to MD (p < 0.001); they were consuming significantly more cereals, legumes, vegetables, and fruits compared to GG. GG consumed significantly more dairy (3.8 ± 2.9 vs. 1.9 ± 2.2, p < 0.001 ) and potatoes (2.4 ± 1.6 vs. 1.9 ± 1.5, p < 0.001 ) compared to GA. Meat ( p = 0.27 ), poultry ( p = 0.72 ), fish ( p = 0.68 ), olive oil ( p = 0.16 ) and alcohol consumption ( p = 0.05 ) were comparable between the two groups (all p's > 0.05). MedDietScore was positively associated with SAI among both groups after adjusting for possible confounders (0.041 ± 0.014, p = 0.003 GG and 0.153 ± 0.035, p < 0.001 GA). Also, legumes, cereals, fruits and vegetables were found to be beneficial for successful aging.Conclusion: Adherence to the MD is associated with higher levels of successful aging among people of the same genetic background living in different environments. However, traditional dietary habits are gradually abandoned in their native countries, when, at the same time, are considered cultural heritage and preserved accordingly among immigrants.